Numerical and experimental investigations of uniform fluid distribution for droplet formation in parallelized microfluidics - Aladese, Adedamola D.; Jeong, Heon-Ho (Frontiers in Sensors, 2022)
Droplet microfluidics, which is the manipulation and handling of fluid in microscale channels, has excellent applications in material science, chemical synthesis, genetic analysis, drug discovery and delivery, organ on chips, and tissue engineering. Consequently, this field has attracted significant attention from both academic institutions and industries. However, one of the major constraints is increasing the droplet production rate from a single generator to thousands of generators in order to move from a laboratory scale to industrial standards. Although the scale-up method (in this case, parallelization) of droplet production using theoretical calculations has been extensively investigated, it has been discovered to be occasionally unreliable during experiments. The use of computational fluid dynamics (CFD) simulation, which has recently been applied to droplet microfluidics, has helped to determine the exact factors and conditions required for uniform droplet formation in flow-focusing devices. Thus far, there has been limited study on the simulation of distribution structures that effectively supply fluids to microfluidic devices in parallel orientation. In this study, CFD is used to provide detailed insights into the conditions required to achieve uniform fluid distribution in the delivery and/or distribution channel of microfluidic devices, and experimental analysis is used to further validate the findings.